Synthesis, Structure and Magnetic Properties of Sm6−xLaxMn23 (0.5 ≤ x ≤ 4) Alloys - Ying-Hua Liang; Zhong Zhang; Jihoon Park; Jia-Cheng Lyu; Hong-Liang Ge; Ping-Zhan Si; Chul-Jin Choi (Magnetochemistry)
The structure and magnetic properties of Sm6−xLaxMn23 (x = 0.5, 1, 2, 3 and 4) alloys have been studied systematically. We found that the Th6Mn23-type Sm6−xLaxMn23 alloys become less stable with increasing La content, and α-Mn becomes the dominant phase at x = 4. More impurities were found to present in Sm5LaMn23 samples prepared by a rapid solidification process than those present in the as-cast ingots. The coercivity of Sm4La2Mn23 induction-melted ingots and Sm5LaMn23 melt-spun ribbons reached up to 0.47 T and 0.53 T, respectively, indicating potential applications of this alloy in hard magnetic materials. The Curie temperature of Sm6−xLaxMn23 falls in the range of 398 K for x = 1 to 438 K for x = 3. The La-substitution results in a reduced saturation magnetization of Sm6−xLaxMn23, owing to a reduced total-magnetic-moment contribution of the Sm-sublattices. This work provides us a deeper understanding of the effect of La-substitution on the structure and magnetic properties of the ternary La-Sm-Mn alloys.